The Challenge of Integrating Tawhid in Science and History: Case Study of Al-Amin Islamic School - Riski Munandar Hutapea; M Husnaini; Tahraoui Ramdane Murad (International Journal of Asian Education, 2021)
This study aimed to highlight the challenge that Secondary School teachers face in integrating the Islamic concept of tawhid in teaching science and history subjects. The research employed a qualitative design using a case study and collect data. A purposive sample consisting of 5 teachers from Al-Amin Islamic Secondary School was selected based on teaching experience. The teachers were interviewed according to a theme-based strategy, and collected data was transcribed and analyzed accordingly. Findings have shown that integrating tawhid in the subjects of Science and History is an aim that teachers in Islamic schools in Malaysia hope to achieve. However, obstacles and challenges continue to hinder their efforts. Theoretical and practical propositions and recommendations to make this aim achievable, such as revisiting the concept of tawhid integration, enhancing teachers' creativity skills in the classroom, and providing relevant training programs by school authorities, would undoubtedly help attain their ultimate objective.